1975
DOI: 10.1071/ar9750937
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection in Australian Merino sheep. VII. Phenotypic and genetic parameters for some wool follicle characteristics and their correlation with wool and body traits

Abstract: Four numerical characteristics-follicle depth, follicle curvature, number of follicles per unit area of skin, and ratio of number of secondary to number of primary follicles-describing the size, shape, and arrangement of wool follicles have been measured in Peppin Merino sheep at 4-5 months (weaning), 15-16 months (two-tooth shearing) and at later ages ranging from 2 1/2 to 7 1/2 years. Estimates of their repeatability, heritability and phenotypic, genetic, and environmental correlations with 10 wool and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
3
10
1
Order By: Relevance
“…This is due to the effect of in utero competition for nutrients on follicle initiation, with fewer secondary follicles being produced in twin-born lambs (Schinckel 1953;Jackson et al 1975;Hocking Edwards et al 1996), although there is some evidence that these differences in the follicle population do not persist in all Merinos (Thompson et al 2007). Furthermore, nutrition of ewes during pregnancy and lactation affects wool production over the life of both single-and twin-born progeny.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the effect of in utero competition for nutrients on follicle initiation, with fewer secondary follicles being produced in twin-born lambs (Schinckel 1953;Jackson et al 1975;Hocking Edwards et al 1996), although there is some evidence that these differences in the follicle population do not persist in all Merinos (Thompson et al 2007). Furthermore, nutrition of ewes during pregnancy and lactation affects wool production over the life of both single-and twin-born progeny.…”
Section: Introductionmentioning
confidence: 99%
“…The weight and diameter of wool produced by sheep is influenced by the ratio of secondary to primary wool follicles and the number of secondary follicles is genetically controlled (Jackson et al 1975;Hocking Edwards et al 1994). Secondary wool follicles are initiated between Day 80 of fetal life and just before birth and most secondary follicles commence producing a fibre 1-3 weeks after birth (Short 1955a;Hocking Edwards 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Despite high correlations between some pelt and follicle characters, selection based on indirect characters has not always resulted in expected responses. For instance, Jackson et al (20) and Rendel and Nay (21) found no increase in clean wool weight when they selected for increased S/P ratio, follicle depth, follicle density, or total follicle number, despite follicle characters changing in the expected direction with selection.…”
Section: Discussionmentioning
confidence: 99%
“…The lambs were born during the spring and were evaluated subjectively for pelt traits (curl type, curl breadth, pattern, luster, color, and final pelt score) by a pelt assessor according to the method described in the guidelines of the Karakul Pelt Assessment Committee of Iran (7). Based on these guidelines, the score of curl breadth in different colors of pelt ranges between 5 and 10 (a score of 5 denotes inferior while a score of 10 denotes excellent), along with scores for luster (5-10), pattern (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), pelt size (0-5), skin thickness (0-5), and curl type , and then the final score of the pelt based on the scores given to the above characteristics is given to the lamb.…”
Section: Methodsmentioning
confidence: 99%